Pengembangan Buku Pendidikan Karakter Rasa Ingin Tahu Dengan Permainan Tradisional Untuk Anak Usia 7–9 Tahun - Amanda, Rosalia; Amanda Utami, Rosalia (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The character education of curiosity is increasingly being eroded due to limited facilities which have an impact on the emergence of serious problems. The aim of this research is to develop a guidebook for traditional games that can improve the curious character of children aged 7-9 years. The research method used is Research and Development (R&D) with the ADDIE approach. This research involved ten certified teachers as respondents to the needs analysis. Apart from that, four lecturers, four certified teachers, traditional game practitioners and artists are also involved as validators of traditional game book products. The subjects involved in this limited research trial were eight children aged 7-9 years. Based on this research, it can be summarized in three main points, namely 1) The product was developed through the ADDIE stages, 2) The quality of the research product obtained an average score of 3.84 and met the criteria "Very good", so "No Revision is Required", and 3) The product is able to influence the curious character of children aged 7-9 years. This is proven by the mean score of the significance test with paired samples t test showing the posttest mean score (M = 3.54688, SE = 0.05716) showing a higher score than the pretest mean (M = 2.2265, SE = 0.014032). The value of t(7) = 9.408, p = 0.000 (p ˂ 0.05), shows a significant difference. The magnitude of the effect (effect size) of r = 0.996 is equivalent to 99% which is included in the "Large Effect" category. The results of the N-gain score analysis were 73.49%, including the "High" criterion.